Communication of crisis or crisis of communication? The conflicting “voices” of the covid 19 pandemic across the world (Altre Modernità, 2022)
After the outbreak of the coronavirus pandemic in China in December 2019, information spread globally as fast as the virus. Different stakeholders confronted daily in the rhetorical arenas of social media within and across countries, thus providing a bewildering view of the impact of COVID-19 on communication. This paper aims at investigating the crisis of communication during the first wave of the pandemic, drawing upon the rhetorical arena communication model (Johansen and Frandsen 2017). This model, which entails a macro- and a micro-layer of analysis, allows us to recognize the complexity of the inter-actorial relations taking place between various “voices”, e.g., political and economic actors, international organizations, healthcare professionals, and the media, who compete or collaborate to manage the crisis. In this regard, research is carried out on a set of corpora, including press releases issued by the WHO, political speeches released by Donald Trump and Boris Johnson, as well as reactions to them provided by public opinion via diverse social media outlets, in the period between January and June 2020. Attention is paid to the micro-level of the arena, in particular some specific “text” parameters, namely the verbal and visual semiotic adopted, the crisis communicative strategies of scapegoating and counterattack, metaphors and speech acts.